Analisis Nilai Tambah dan Manajemen Industri Ikan Pindang Tongkol di Kecamatan Rancaekek, Kabupaten Bandung (Studi Kasus: UMKM Pindang Pelem) - Lisa Gabriela; Junianto (Jurnal Serambi Engineering, 2024)
Indonesia is rich in fish resources, both in terms of species and quantity. Fish processing is a critical step in maintaining the quality and adding value to fishery products. Brine boiling is a traditional fish processing technique used to extend shelf life and enhance flavour. This study aims to analyse the added value and management of mackerel tuna brine boiling industry at UMKM Pindang Pelem. The research was conducted at the UMKM Pindang Pelem Production House in March 2024. The method used in this study is a descriptive case study. The Hayami method was used to analyse the value added of brine cooked mackerel tuna fish products. The analysis showed that the production of brine boiled mackerel tuna fish at UMKM Pindang Pelem has a value added ratio of 15.18%, with a profit margin of 60.78%. UMKM Pindang Pelem's management practices include sourcing fresh mackerel tuna from suppliers in Pasar Induk Caringin and Pasar Parakanmuncang. An efficient production process results in brine-cooked mackerel tuna products that are competitive in terms of taste, flavour and cleanliness. UMKM Pindang Pelem uses static attribute segmentation for market strategy and cost plus pricing for product pricing. The marketing strategy includes promotions via WhatsApp and word of mouth.